1994
DOI: 10.1143/jjap.33.1346
|View full text |Cite
|
Sign up to set email alerts
|

Reflection Mode Polymer-Dispersed Liquid Crystal Light Valve

Abstract: We study the level spacing distribution p(s) in the spectrum of random networks. According to our numerical results, the shape of p(s) in the Erdős-Rényi (E-R) random graph is determined by the average degree k and p(s) undergoes a dramatic change when k is varied around the critical point of the percolation transition, k = 1. When k 1, the p(s) is described by the statistics of the Gaussian orthogonal ensemble (GOE), one of the major statistical ensembles in Random Matrix Theory, whereas at k = 1 it follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Takizawa et al reported a photonic application of the LMWLC/polymer composite fi lms: a spatial light modulator (SLM) that displays large images on a screen by projecting an image created on a small valve. [ 66 ] Kajiyama et al showed light addressing and optical image recording by means of LMWLC/polymer composite fi lms showing electric fi eld frequency-dependent optical properties. [ 67 ] In confi ned polymer matrices by microphase separation, the photocontrollable LMWLC/polymer composite fi lms driven by photon-mode process without electric fi elds have been achieved via photochemical phase transitions.…”
Section: Photoinduced Phase Transition In Lmwlc/polymer Compositesmentioning
confidence: 99%
“…Takizawa et al reported a photonic application of the LMWLC/polymer composite fi lms: a spatial light modulator (SLM) that displays large images on a screen by projecting an image created on a small valve. [ 66 ] Kajiyama et al showed light addressing and optical image recording by means of LMWLC/polymer composite fi lms showing electric fi eld frequency-dependent optical properties. [ 67 ] In confi ned polymer matrices by microphase separation, the photocontrollable LMWLC/polymer composite fi lms driven by photon-mode process without electric fi elds have been achieved via photochemical phase transitions.…”
Section: Photoinduced Phase Transition In Lmwlc/polymer Compositesmentioning
confidence: 99%
“…Because of their many attractive features, 1-3 PDLC films are regarded as potential candidates for use in large-area displays, 4,5 optical shutters, and other light-controlling devices. 6,7 At present, polymerization-induced phase separation is a popular method for the preparation of PDLC films. The reaction of the network formation may be chain polymeriza-tion or step polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…PDLCs, have been a subject of interest in the study of surface effects and phase separation, because of the nonlinear behavior of such systems, since their optical properties can be controlled by the optical electric field [9, 10]. PDLCs have a wide variety of applications due to their peculiar electro‐optical and mechanical properties: smart windows [11, 12], spatial light modulators [13], direct‐view displays [14], projection displays [15], eye‐protection viewer device [16], sensors etc. The electro‐optical and mechanical properties of the PDLCs can be enhanced by choosing or designing carefully the material selected.…”
Section: Introductionmentioning
confidence: 99%